Investment decision rules in a competitive market and in the case of co-opetition. The real options games approach - Rychłowska-Musiał, Elżbieta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The main goal and the original role of this paper were to find and describe decisional rules used by firms based on the net present value of an investment project and on the investment option value for different market conditions (competition or co-opetition). The investment decision-making process is described as a game between two players, while the real options analysis (ROA) is used to find the value of an investment project, thus the paper falls in the category of real options games (ROG). An analysis of these games may help explain some of the aspects of a firm’s behaviour and offer some guidelines to managers. In a purely competitive environment, a firm will not delay execution of the project because of the risk of being outdistanced by competitors. In this case, firms will be interested in using the real option framework in their decision-making process only when the classic NPV is definitely negative, even if the real option theory recommends using it in some cases when NPV is positive. A co-opetition case offers much better prospects for the application of ROA. The introduction of cooperation arrangements among competitors reduces the area of conflict of interest between them. Firms that build a co-opetition relationship should be more interested in using the real options approach. Nevertheless, it should be emphasised that while the risk of the project is high, the creation of a co-opetition relationship requires much more attention and consideration due to the threat of contract termination. Nonetheless the benefits that firms enjoy by following a co-opetition agreement are more substantial only in the case of high-risk projects. An additional innovative contribution of the paper is taking into account the interactions between the model parameters. This is essential in performing a sensitivity analysis and it reflects the links observed in practical applications
Argumenta Oeconomica, 2019, Nr 2 (43), s. 329-350
Keywords: real options; investment option; competition; co-opetition; real options games; game theory